2013
DOI: 10.3762/bjoc.9.208
|View full text |Cite
|
Sign up to set email alerts
|

Flow Giese reaction using cyanoborohydride as a radical mediator

Abstract: SummaryTin-free Giese reactions, employing primary, secondary, and tertiary alkyl iodides as radical precursors, ethyl acrylate as a radical trap, and sodium cyanoborohydride as a radical mediator, were examined in a continuous flow system. With the use of an automated flow microreactor, flow reaction conditions for the Giese reaction were quickly optimized, and it was found that a reaction temperature of 70 °C in combination with a residence time of 10–15 minutes gave good yields of the desired addition produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In pursuit of a potential substitute for tin hydride, we envisioned that radical methodologies based on borohydride as the hydrogen donor would have great potential and would be quite useful. In our preliminary communication, we reported that the reductive addition of alkyl radicals to electron-deficient olefins , and the related carbonylation reactions proceeded in the presence of cyanoborohydride reagents as radical mediators (Scheme ). We also reported the radical hydroxymethylation of alkyl iodides with CO or HCHO .…”
Section: Introductionmentioning
confidence: 99%
“…In pursuit of a potential substitute for tin hydride, we envisioned that radical methodologies based on borohydride as the hydrogen donor would have great potential and would be quite useful. In our preliminary communication, we reported that the reductive addition of alkyl radicals to electron-deficient olefins , and the related carbonylation reactions proceeded in the presence of cyanoborohydride reagents as radical mediators (Scheme ). We also reported the radical hydroxymethylation of alkyl iodides with CO or HCHO .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Zheng and Guo reported that TMEDA-catalyzed radical arylation of benzene under photoirradiation conditions with high tolerance of functional groups . Recently, we reported radical C–C bond-forming reactions using borohydride reagents as chain mediators. , In this paper, we report that cyanoborohydride promotes the synthesis of biaryl compounds from iodoarenes and benzene under aerobic photoirradiation conditions. This reaction proceeds in a chemoselective fashion for bromo- and iodo- substituted arenes.…”
mentioning
confidence: 72%
“…The flow reaction system has been recognized as a useful platform for organic chemistry as well as pharmaceutical, chemical industries . These flow reaction systems with high ratio of surface area to volume have unique features, such as efficient transfers of heat and mass, enabling diverse green and sustainable chemical processes . The precise control of reaction time is one of the most outstanding advantage of the flow‐synthetic methods.…”
Section: Comparative Performance Of Anionic Fries Rearrangement Reactmentioning
confidence: 99%